PENGEMBANGAN USAHA PRODUK TEH BERAS MERAH KELOMPOK WANITA TANI KUNTUM SARI DIDUSUN WONGAYA BETAN, MENGESTA, PENEBEL, TABANAN, PROVINSI BALI. - Putu Ledyari Noviyanti; Desak Ayu Sriary Bhegawati (Bahasa Indonesia, 2019)
Abstract Tea is they get milk to drink the most mostly consumed in the world after the water , being drinkable in asia for more than 4000 years .One of a group of of the business to which producing tea in the form of rice the reds are of a group of the village or are farm woman KWT Kuntum Sari situated holds true in Dusun Wongaya Betan , Desa Mengesta , Kecamatan Penebel Kabupaten Tabanan Bali .The main problems that is experienced KWT provision and preparation for the producing tea in the form of rice red the following are a problem with marketing the product .From the matter so as tea leaves are set in red monday order by the business rice are likely to expand muamalat ran into financial difficulties review the import facility granted for the best solution of meet the goal of providing media training of marketing for member of KWT Kuntum Sari, as well as were given training to good financial management will be given attending to the duties of the import and the registration of expenditure . Abstrak Teh merupakan minuman paling banyak dikonsumsi di dunia setelah air, yang diminum di Asia selama lebih dari 4000 tahun. Salah satu kelompok usaha yang memproduksi teh beras merah adalah dari Kelompok Wanita Tani (KWT) Kuntum Sari terletak di Dusun Wongaya Betan, Desa Mengesta, Kecamatan Penebel Kabupaten Tabanan Bali. Permasalahan utama yang dialami KWT ini selama memproduksi Teh Beras Merah berikut adalah masalah pemasaran produk. Dari permasalahan tersebut agar usaha teh beras merah berkembang diberikan solusi yaitu pengadaan pelatihan media pemasaran untuk ibu-ibu anggota KWT Kuntum Sari, serta diberikan pelatihan manajemen keuangan baik pencatatan pemasukan dan pencatatan pengeluaran.